Editorial: Penetration of food protein through the oesophageal mucosa—is this where EoE starts?. Issue 3 (11th January 2021) - Uchida, Amiko M.; Dougan, Michael
Abstract : LINKED CONTENT This article is linked to Ravi et al and Ravi & Katzka papers. To view these articles, visit https://doi.org/10.1111/apt.16180 and https://doi.org/10.1111/apt.16223